The role of independent directors and their appoinment process - Rahman, Anis Ur (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
The issue of appointing independent directors arose due to larger/controlling shareholders dominating the board and ignoring the rights of the minority shareholders. The revised Malaysian Code of Corporate Governance 2012 emphasizes the importance of independent directors and their independence at the workplace. Independent directors have the desired qualities that may help the board discharge its duties effectively whilst improving the effectiveness of the boardroom. This study explores the roles of the independent directors and their appointment process among PLCs in Malaysia. To this end, semi-structured interviews were conducted to understand the role of independent directors and their appointment process in PLCs under Bursa Malaysia. This study finds that independent directors play two significant roles. The first is a monitoring role in line with agency theory. The second one is an advisory role which in line with resource dependency theory. Thus, it may conclude that monitoring and advising are indispensable roles that independent directors are supposed to play effectively. The findings of the study revealed independent directors are pivotal in monitoring top management, major/controlling shareholders, reducing conflict of interest, protect shareholders wealth, and executing independent judgment for all shareholders. In terms of appointment process, this study found that the personal qualities of the candidates are very important. The board desires experience, expertise, professionally qualified, and reputable persons who can commit to their tasks. In terms of re-appointment, boards consider the contribution of the independent director rather than their tenure. The board does not consider race, religion, and gender as selection criteria. Based on the result of the study, all have the opportunity to sit on the board if he/she is qualified. As such, the role of the nomination committee is indispensable to select and propose the new independent director; however the board will make the final decision for appointing the new independent director.